Association between the ratio of triglycerides to high-density lipoprotein cholesterol and nocturnal hypertension: a cross-sectional study in a Chinese population - Dong, Hezeng; Liu, Zhaozheng; Zhang, Jinling; Han, Ye; Zhang, Jing; Xi, Yazhi; Chang, Liping; Deng, Yue (Frontiers in Endocrinology, 2025)
Background and objectiveThe ratio of triglycerides to high-density lipoprotein cholesterol (TG/HDL-C) serves as a predictive indicator for metabolic syndrome and cardiovascular diseases. Simultaneously, nocturnal hypertension significantly increases the risk of target organ damage and cardiovascular events. However, the relationship between the TG/HDL-C ratio and nocturnal hypertension remains unclear. Therefore, the present study aimed to determine the efficacy of the TG/HDL-C ratio in predicting the occurrence of nocturnal hypertension and reducing related adverse events.MethodOur rigorous cross-sectional study, which included 749 participants who underwent 24-hour ambulatory blood pressure monitoring at the Cardiology Center of Changchun University of Chinese Medicine Affiliated Hospital, allowed us to determine the association between the TG/HDL-C ratio and nocturnal hypertension. We employed both univariate and multivariate logistic regression analyses to ensure the robustness of our findings. Logistic regression modeling was used to assess the independent predictive ability of TG/HDL-C for nocturnal hypertension while adjusting for confounders such as sex, age, BMI, and smoking status. Model performance was assessed by subject work characteristics (ROC) curves and area under the curve (AUC).ResultsAmong the 749 participants included in this study, 566 were identified with nocturnal hypertension. Univariate logistic regression analysis demonstrated that the TG/HDL-C ratio was positively correlated with the occurrence of nocturnal hypertension, with the risk of nocturnal hypertension increasing by 24% (OR 1.24(1.06-1.45), P=0.006) for every 1-unit increase in the TG/HDL-C ratio. After adjusting for past medical history, medication, and other relevant examinations, a multivariate analysis revealed a significant correlation between the TG/HDL-C ratio and nocturnal hypertension. Logistic regression analysis demonstrated that TG/HDL-C was positively associated with nocturnal hypertension (regression coefficient = 0.115, P < 0.05). After adjusting for sex, age, BMI, and smoking status, TG/HDL-C remained a predictor of nocturnal hypertension.ConclusionOur study underscores the significant association between an elevated TG/HDL-C ratio and the occurrence of nocturnal hypertension. This finding has the potential to draw the attention of patients and physicians to lipid levels, particularly among males, individuals over 45 years old, those with a BMI greater than 24, smokers, and those with a history of hypertension. An independent positive association between TG/HDL-C and nocturnal hypertension was also determined using logistic regression modeling. The findings suggests that it may have potential application in the early screening of nocturnal hypertension. However, the predictive ability is limited, and further studies are necessary to incorporate larger sample sizes and longitudinal designs. These additional studies would validate the predictive role of TG/HDL-C and explore its biological mechanisms.